Analysis Of The Financial Performance Of Islamic Commercial Banks In Indonesia Using The Sharia Conformity And Profitability (SCNP) Method For The 2021–2024 Period - Yusuf, Amaliyah; Arifai, Samsul; Ismawati, Ismawati; Zaldira, Aina (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study is motivated by the measurement of Islamic Commercial Bank performance which is still more oriented toward profitability than compliance with sharia principles. This study aims to analyze the level of sharia compliance, profitability, and the balance between both aspects in Islamic Commercial Banks in Indonesia during the 2021–2024 period using the Sharia Conformity and Profitability (SCnP) method. This research uses a quantitative method with a descriptive approach based on annual financial statement data from Bank Syariah Indonesia, Bank Muamalat Indonesia, Bank BCA Syariah, and Bank Mega Syariah for the 2021–2024 period. The results show that Bank Syariah Indonesia tends to be in the Upper Left Quadrant (ULQ), indicating high profitability but sharia compliance still needs improvement. Bank Muamalat Indonesia and Bank BCA Syariah are more dominantly positioned in the Lower Right Quadrant (LRQ) because they have high sharia compliance but relatively low profitability. Meanwhile, Bank Mega Syariah demonstrates more stable development with an increasing balance between sharia compliance and profitability. This study concludes that not all Islamic Commercial Banks have been able to achieve an optimal balance between sharia compliance and profitability. The implications of this study indicate the importance of improving the balance between financial performance and the implementation of sharia principles in order to achieve optimal, competitive, and sustainable Islamic banking performance amid the development of the Islamic banking industry in Indonesia.